(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the methodological foundations and empirical aspects of developing learner autonomy in English Language Teaching within a digital learning environment. It explores key theoretical frameworks, including constructivism, humanistic education, and self-regulated learning theory. The study highlights the pedagogical potential of digital environments, such as accessibility, personalization, and interactivity, in fostering independent learning skills. Additionally, modern teaching approaches–blended learning, flipped classroom, project-based learning, and gamification–are analyzed in terms of their effectiveness in promoting learner autonomy. Empirical findings from Uzbekistan indicate that digital technologies significantly enhance autonomous learning. The article also discusses major challenges, including the digital divide and insufficient self-regulation skills. Finally, practical strategies for supporting learner autonomy are proposed.